Synthesis and characterization silica-MB@GO-NH2 particle as fluorescence-based chlorine sensor - Fatah, Fadhlir Rahman Aufar Al; Rahmawati, Isnaini; Gunlazuardi, Jarnuzi; Sanjaya, Afiten Rahmin (Environmental and Materials, 2023)
In this research, we developed a fluorescence-based sensor to determine the sodium hypochlorite concentration (NaOCl) in tap water and swimming pool water samples. The detection of NaOCl was conducted by measuring the luminescence response of analyte in the paper-based sensor modified Silica-MB@GO-NH2 material were synthesized using Hummer's and Stober's methods under UV Light irradiation. Additionally, the prepared material exposed a couple peak 2D and 2G at 2938 cm-1 and 3286 cm-1 with ID/IG ratio 0.98 using Raman characterization which appropriate with the presence of GO structure in the mixture. This result was validated by the appearance of several functional groups like Si-O-Si, NH, OH, and C-C at 1079, 1391, 1611, and 3457 cm-1, respectively. Moreover, the existence of Si-O-Si bond indicates that the silica-MB interaction was perfectly formed, which plays the main role to absorb ultraviolet light that is used as sensor probe. The morphology of particles depicted an aggregated formation of spherical structure with 288 nm particle size, indicating the existence of silica-coated methylene blue. In this work, the paper-based sensor modified Silica-MB@GO-NH2 can detect the NaOCl species with concentration range 10-150 µM (R2 = 0.9757), a detection limit at 2.60 µM and quantification limit at 7.88 µM. Furthermore, this developed sensor has stable measurement with recovery performance 3.65%-6.67% for tap water and 0.05%–0.14% for swimming pool water. This result indicates that the prepared sensor can be potentially applied to calculate the hypochlorite species in the aquatic environment.